Engaging Parental Responsibility and the Moral Problems in Contemporary Nigeria from the Backdrop of Proverbs 22: 6 - Omosor, Festus Osom (dialektika kontemporer, 2025)
This paper examines the connection between parental responsibility and rising moral challenges in contemporary Nigeria from the backdrop of Proverbs 22:6, which addresses the role of parents in teaching morals and spirituality. This study argues that the decline of societal ethics, including corruption, indiscipline, and the erosion of communal integrity, finds its origin primarily in the collapse of family-nurtured moral education and the neglect of biblical doctrine that once informed Nigerian homes. With a theological and socio-cultural approach, the paper looks at how value distortion and moral dissent among children have been brought about by modernization, globalization, and the breakdown of parental authority. Proverbs 22:6 is an enduring paradigm for restoring moral order, focusing on early and intentional moral instruction based on faith and example. The paper highlights the central position of parents as moral guardians and calls for collaborative efforts by families, religious institutions, schools, media, and government towards effecting moral reformation. It asserts that the moral reformation of Nigeria must begin at the family level, where integrity, discipline, and godliness are imparted. Lastly, a comeback to the wisdom of Proverbs 22:6 is a spiritual and practical means to rehabilitate a fair, accountable, and ethical society.